GREEN BUSINESS MODELS FOR SMALL ENTERPRISES IN UZBEKISTAN: LESSONS FROM DEVELOPED COUNTRIES (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This paper analyzes the concept of green business models, explores experiences from developed countries, and examines how such models can be adapted to small enterprises in Uzbekistan. The aim of the study is to identify business approaches that harmonize ecological sustainability with economic efficiency and to demonstrate how they can be practically applied in Uzbekistan. The article reviews the experiences of Germany, Sweden, and South Korea, and adapts them to the local context of Uzbekistan. The findings indicate that South Korea’s system, based on grants and tax incentives, can be most effectively implemented in Uzbekistan, considering the financial limitations of small businesses. The paper also provides practical recommendations for expanding green financing among small enterprises.